2022
DOI: 10.1002/slct.202202721
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Mineralization of Metal Ion‐Doped Lipase into ZIF‐8 Framework for Enhanced Hydrolytic Activity in Biphasic System

Abstract: Present work encapsulated metal ion dopped‐Candida rugosa lipase (CRL) into ZIF structure through biomimetic mineralization and evaluated hydrolytic activity of the immobilized lipase using a biphasic system. Magnesium ion (Mg2+) doped‐CRL with high hydrolytic activity (237 % of free CRL) was successfully synthesized. Circular dichroism and fluorescence spectroscopy analysis revealed Mg2+ doping has changed the conformation of CRL resulted in enhanced structural stability of CRL. The synthesized CRL/Mg2+@ZIF‐8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In fact, a high stoichiometric ligand/Zn 2+ applied in the synthesis of esterase@MAF-6 and esterase@ZIF-8 ensures a high crystalline MOF shell over esterase with minimum defects, supporting a fair bioactivity comparison between esterase@ZIF-8 and esterase@MAF-6. Hydrolase@ZIF-8 (e.g., BCL@ZIF-8 (BCL = Burkholderia cepacia lipase), CALB@ZIF-8 (CALB = Candida antarctica lipase B), CRL@ZIF-8 ( Candida rugosa lipase), lipase@ZIF-8 , ) can also be synthesized under a low molar HmIM/Zn ratio (HmIM/Zn ≈ 4). However, spectroscopic and microscopic analysis demonstrated that protein@ZIF-8 samples synthesized under a low HmIM/Zn condition were rich in amorphous phase and coordination defect, which result in larger opening pores than the intrinsic pore structure of ZIF-8. , The minimal structural defects in ZIF-8 and MAF-6 were supported by TGA analysis (Figure S10–S11).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a high stoichiometric ligand/Zn 2+ applied in the synthesis of esterase@MAF-6 and esterase@ZIF-8 ensures a high crystalline MOF shell over esterase with minimum defects, supporting a fair bioactivity comparison between esterase@ZIF-8 and esterase@MAF-6. Hydrolase@ZIF-8 (e.g., BCL@ZIF-8 (BCL = Burkholderia cepacia lipase), CALB@ZIF-8 (CALB = Candida antarctica lipase B), CRL@ZIF-8 ( Candida rugosa lipase), lipase@ZIF-8 , ) can also be synthesized under a low molar HmIM/Zn ratio (HmIM/Zn ≈ 4). However, spectroscopic and microscopic analysis demonstrated that protein@ZIF-8 samples synthesized under a low HmIM/Zn condition were rich in amorphous phase and coordination defect, which result in larger opening pores than the intrinsic pore structure of ZIF-8. , The minimal structural defects in ZIF-8 and MAF-6 were supported by TGA analysis (Figure S10–S11).…”
Section: Resultsmentioning
confidence: 99%